L’Anselmo di Hans Urs von Balthasar. L’analogia entis maturata nel dialogo con K. Barth e riletta come analogia libertatis - Villagrasa LC, Jesús (Alpha Omega, 2010)
The figure of Anselm sheds light on some aspects of the comparison between Karl Barth and Hans Urs von Balthasar with regard to the theme of analogy. Barth’s work Anselm strongly influenced von Balthasar, yet neither conditioned nor limited the originality of the famous Catholic theologian. In his work Gloria, Balthasar tried to legitimate a theological aesthetics in which Anselm is one of the most illustrious representatives. According to Balthasar, an intellectual evolution occurs in Anselm, who is seen to depart from the «necessary reasons» of theology and give increasing importance to the truly theological theme of freedom, namely, to the relationship of the Absolute Being with relative being in the light of the self-opening of the Absolute. In Anselm the philosophical analogia entis becomes the theological analogia libertatis. The whole of theological discourse is founded upon a simple vision of the analogia libertatis between God and creature.